MAPPING HISTORICAL DIALOGUE: Remembering for the Future. - Atkinson-Phillips, Alison; Capdepón, Ulrike; Strauss, Jill; López-Badell, Oriol (Kritika Kultura, 2020)
The Mapping Historical Dialogue Project (MHDP) was developed in 2014, as part of a larger initiative relating to historical dialogue and accountability housed at Columbia University's Institute for the Study of Human Rights. In the months and years that followed, a group of scholars and practitioners from ten different countries and representing all continents served as researchers to the project. The four authors of this essay are amongst this core group. The Mapping Historical Dialogue is a global interactive geographical map that gathers information on projects of contested memory in (post-)violent conflict countries. The ongoing digital project builds on a crowdsourcing model, relying on incremental contributions to connect a diverse network of individuals who often do not have access or knowledge of one another's work. This paper gives an overview of the development of the mapping project and then outlines some of the diverse historical dialogue initiatives that speak to questions of memory, transitional justice, and human rights. The article offers insights into different regional contexts and countries, suchas colonization and aboriginal trauma in Australia, slavery in the United States, the legacy of the Civil War "disappeared" and the Franco dictatorship in Spain, including the example of the EUROM network led by the University of Barcelona, as well as examples of the human rights movement in the Southern Cone countries, Chile and Argentina.